Management of Clavicle Fractures and Adjacent Clavicular Joint Dislocations in a Tertiary Health Center, North West, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Fractures of the clavicle are known to be common and occur in all ages and genders. It is commoner in the young and elderly, especially postmenopausal women. The mechanism of injury is either direct resulting in transverse fracture or indirect resulting in oblique fracture. The results of treatment are more favorable in the younger age groups because of their inherent healing potentials compared with the elderly.Aims and Objectives:To assess the incidence of clavicle injuries, treatment modalities with their outcomes, and to evaluate the X-ray union of the pathology.Patients and Methods:The patients were recruited over a period of 4 years (2009–2012) with informed and duly signed consent obtained. Fractures or dislocations were confirmed clinically and radiologically. One group of the patients was managed conservatively and the other operatively with various surgical options.Results:A total of 49 patients comprising 34 males (69.4%) and 15 females (30.6%) were studied. The age range was 2 weeks (0.6 years) to 62 years (mean- 32.1 years). Middle third shaft fractures were the commonest (77.6%), while medial third shaft fractures and acromioclavicular joint dislocation were the least common (2.0% each). Thirty-three (67.3%) and 16 (32.7%) of the patients were managed conservatively and operatively, respectively. The average X-ray healing duration was 16.2 and 14.6 weeks for those managed conservatively and surgically, respectively.Conclusion:Middle third clavicle fractures constitute the commonest variety, and both conservative and operative treatment modalities are applicable.